Trends of participation of post-graduate year training program for dentists in Taiwan dental training institutions from 2010 to 2018 - Feng-Chou Cheng; Chun-Pin Chiang; Tzu-Chiang Lin; Wen-Chiung Chang; Eddie Hsiang-Hua Lai; Yung-Ta Chang (Elsevier, 2019)
Background/purpose: The licensed dentists in Taiwan should join the post-graduate year training program for dentists (PGYD) since 2010. This study aimed to analyze the project types and the geographical distribution of the PGYD training institutions in Taiwan from 2010 to 2018. Materials and methods: From 2010 to 2018, 735 hospitals and clinics participated in four types of PGYD project including hospital as the single training institution (project A), clinic as the single training institution (project B), hospital as the main training institution in the joint training group (project C), and clinic as the main training institution in the joint training group (project D). The project types and the geographical distribution of the training institutions were analyzed. Results: The 735 PGYD training projects were proposed by the 735 dental institutions. The project number grew from 119 in 2010 to 195 in 2018. The most common project type was project B (307, 41.8%), followed by the project A (249, 33.9%), the project D (101, 13.7%), and the project C (78, 10.6%). Geographically, these 735 main training institutions were located most commonly in northern region of Taiwan (379, 51.6%), followed by the central region of Taiwan (171, 23.3%), southern region of Taiwan (156, 21.2%), and eastern region of Taiwan (29, 3.9%). Conclusion: Hospital or clinic as the single training institution is the two most common PGYD project types in Taiwan from 2010 to 2018. These single or main dental training institutions are mainly located in the northern, central, and southern regions of Taiwan. Keywords: Post-graduate year training program for dentists, Clinical dental training project, Clinical dental training institution, Collaborating dental training institution